Long-term voice results of injection with hyaluronic acid-dextranomere in unilateral vocal fold paralysis. (May 2013) - Oguz, Haldun; Demirci, Munir; Arslan, Necmi; Arslan, Erhan
Abstract Conclusion: Subjective and objective voice evaluation of patients injected with hyaluronic acid-dextranomere (HA-D) in the long term was not different from their preoperative values. HA-D injection does not provide an increase in the voice quality in the long term. Objective: This study was conducted to evaluate the long-term voice outcomes of injection with HA-D in patients with unilateral vocal fold paralysis (UVFP). Methods: Seventeen patients with UVFP underwent injection of HA-D. The patient group was composed of 13 women and 4 men with an age range of 34–56 years. The voice samples of patients were obtained before the injection and after the longest available follow-up. Long-term results were evaluated subjectively by the GRBAS scale and objectively by acoustic analysis. Results: The follow-up period was between 6 and 42 months. Fundamental frequency, jitter, and noise-to-harmonics ratio were decreased in the postoperative period. Shimmer was nearly the same. An increase in the S score and a decrease in R, B, and A scores were observed. Neither the GRBAS scale parameters nor the acoustic analysis results were statistically significantly different before injection and after long-term follow-up.